PENDIDIKAN ISLAM BERKEMAJUAN DALAM PEMIKIRAN HAEDAR NASHIR - Sarno Hanipudin (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2020)
This research examines the Concept of Advanced Islamic Education in the View of Haedar Nashir. The focus of the research that was reviewed is how Haedar Nashir views the concept of Advanced Islamic Educators. This type of research is library research which is a pure library research. Thus the collection of data in this study is to use documentation methods that look for data on things or variables in the form of records such as books, magazines, documents, articles, words, daily minutes, meeting notes and so on.